Examining the Relationship between Corporate Governance Characteristics and Firm Financial Performance: Evidence from UK FTSE 250 - Pan, Yuanyuan (2020)
This dissertation examines the relationship between corporate governance characteristics and firm financial performance. The data was collected from the UK FTSE 250, including 17 significant sectors and crossing nine fiscal years from 2011 to 2019. And the number of sample firms is 122, so spanning nine fiscal years, there are 122*9=1098 observations. The board of directors' characteristics is employed to represent corporate governance, including the board size, the directors' remuneration, gender diversity and the proportion of non-executive directors. At the same time, the firm's profitability ratios serve as the financial indicators, such as Return on Assets (ROA) and Return on Capital Employed (ROCE). The main statistical technique is the fixed-effects regression model, and the ordinary least squares (OLS) regression model is used for robustness tests. The findings show that the relationship between the directors' remuneration and firm financial performance is significantly positive. Furthermore, the proportion of non-executive directors also has a positive influence on the financial performance of a firm. However, the association between board size and corporate performance is significantly negative. And the impact of the presence of female directors on the board on the firm financial performance is negative.